(untitled) (Impetus, 2026)
In recent decades Latin America has been passing through an epistemological emancipation period, motivated by diverse decolonial philosophical contributions. This allows younger generations to become aware of colonial-embedded problems such as capitalism, patriarchy, and racism. It is possible to refer to different endeavours encouraging a liberating Latin American pedagogy, including the corporal dimension. This is also reflected in Physical Education context, from which have emerged new trends and pedagogical experiences. From here, this study aims to reflect on some basis of corporal pedagogies with decolonial and popular meanings from a Latin American epistemological perspective. To reach this objective, there is a discussion developed in two sections. The first section focuses on decolonial meanings by considering the roots of modern Physical Education and their respective oppressions. In order to contribute to overcome colonial rationalities, practical examples are mentioned and problematized. The second section focusses on the meaning of popular education, its theorization, and practical examples that could contribute to its promotion. The final considerations point out that corporal pedagogies with decolonial and popular meanings have a great potential to be strengthened. However, the dialogue, reflection, and research must align with this kind of experience.